Demographic, psychiatric, and personality correlates of adults seeking treatment for disordered gambling with a comorbid binge/purge type eating disorder. (24th May 2018) - Kim, Hyoun S.; von Ranson, Kristin M.; Hodgins, David C.; McGrath, Daniel S.; Tavares, Hermano
Abstract: Preliminary evidence suggests that binge/purge type eating disorders and gambling disorder may commonly co‐occur. However, this dual‐diagnosis population remains understudied. The present research examined the prevalence rates and correlates of binge/purge type eating disorders (i.e., bulimia nervosa, binge‐eating disorder, and anorexia nervosa binge/purge type) among adults seeking treatment for their gambling ( N = 349). In total, 11.5% of the sample ( n = 40) met criteria for a binge/purge type eating disorder, most commonly bulimia nervosa ( n = 33). There was a higher preponderance of binge/purge type eating disorders in women. People with a comorbid binge/purge type eating disorder reported more days gambling, gambling‐related cognitive distortions, impulsivity, suicidality, and other current psychiatric comorbidities including addictive behaviours. These findings suggest that binge/purge type eating disorders in people seeking treatment for gambling may be more common than previously believed. Furthermore, the increased psychopathology among people with binge/purge type eating disorder and gambling disorder identify vulnerabilities of this dual‐diagnosed population that may require clinical attention.